2016
DOI: 10.1108/cdi-10-2015-0131
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of work engagement among high potential employees

Abstract: Purpose The implicit assumption since the beginning of the science and practice of human resource management (HRM) has been that if we do HRM well, this will somehow make organizations perform more effectively. The purpose of this paper is to address this “somehow” by investigating the antecedents of work engagement among high potential employees. Design/methodology/approach The data were collected through a web-based survey from 439 high potential employees of 11 Finnish multinational enterprises. Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Chamorro-Premuzic, Adler, & Kaiser [37] stated that investing in the high potential employees will maximize organizational profits. [33], [34], [36] and [37] consider HiPos as strategic asset for the organizations, supporting the notion why it is necessary to retain high potential talent based on their relative proficiencies. However these studies did not account for HiPo identification and neither they predicted their turnover intention, which limits their application for star identification through social networks.…”
Section: ) Hiposmentioning
confidence: 71%
See 3 more Smart Citations
“…Chamorro-Premuzic, Adler, & Kaiser [37] stated that investing in the high potential employees will maximize organizational profits. [33], [34], [36] and [37] consider HiPos as strategic asset for the organizations, supporting the notion why it is necessary to retain high potential talent based on their relative proficiencies. However these studies did not account for HiPo identification and neither they predicted their turnover intention, which limits their application for star identification through social networks.…”
Section: ) Hiposmentioning
confidence: 71%
“…The dynamic modelling of employee's workplace social interactions for HiPo and Influencer identification differs from the previous work done by [62] and [36]. They followed a subjective approach for identifying the star employees such as manager's intuitive judgement, employees past performance, gauging social skills and personality assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Khoreva and Zaik, 2016). Scholars like Backhaus &Tikoo, (2004)Chi &Gursoy, (2009), Kosteas, (2011), and Curtis & Glacken, (2014) have found that employees will not leave their organization if they are satisfied and are as well as less absent, and show increased in their productivity at work.…”
mentioning
confidence: 99%